Salidroside Attenuates Denervation-Induced Skeletal Muscle Atrophy Through Negative Regulation of Pro-inflammatory Cytokine - Wu, Changyue; Tang, Longhai; Ni, Xuejun; Xu, Tongtong; Fang, Qingqing; Xu, Lai; Ma, Wenjing; Yang, Xiaoming; Sun, Hualin (Frontiers in Physiology, 2019)
Skeletal muscle atrophy is associated with pro-inflammatory cytokines. Salidroside is a biologically active ingredient of Rhodiola rosea, which exhibits anti-inflammatory property. However, there is little known about the effect of salidroside on denervation-induced muscle atrophy. Therefore, the present study aimed to determine whether salidroside could protect against denervation-induced muscle atrophy and to clarify potential molecular mechanisms. Denervation caused progressive accumulation of inflammatory factors in skeletal muscle, especially interleukin 6 (IL6) and its receptor, and recombinant mouse IL6 (rmIL6) local infusion could induce target muscle atrophy, suggesting that denervation induced inflammation in target muscles and the inflammation may trigger muscle wasting. Salidroside alleviated denervation-induced muscle atrophy and inhibited the production of IL6. Furthermore, the inhibition of phosphorylation of signal transducer and activator of transcription 3 (STAT3), and the decreased levels of suppressor of cytokine signaling (SOCS3), muscle RING finger protein-1 (MuRF1), atrophy F-box (atrogin-1), microtubule-associated protein light chain 3 beta (LC3B) and PTEN-induced putative kinase (PINK1) were observed in denervated muscles that were treated with salidroside. Finally, all of these responses to salidroside were replicated in neutralizing antibody against IL6. Taken together, these results suggest that salidroside alleviates denervation-induced inflammation response, thereby inhibits muscle proteolysis and muscle atrophy. Therefore, it was assumed that salidroside might be a potential therapeutic candidate to prevent muscle wasting.